Application of adhesives in wood industries / Suria Mohamad Akhir - Mohamad Akhir, Suria (2004)
A literature search was conducted on the application of adhesives in wood industries to fulfill the requirement of the final project. In wood industries, application of adhesives it so important for bonding one face to another face. There are many types of adhesives that use follows the types of product to produce in wood-based industries. There are different applications of adhesives where it uses either interior or exterior uses. Study for application of adhesives in three countries shows that application for certain types of adhesives depend on what products are produced.